Mixing-performance evaluation of a multiple dilution microfluidic chip for a human serum dilution process - Thienthong, Therdthai; Juntasaro, Ekachai; Sripumkhai, Witsaroot; Houngkamhang, Nongluck; Chanasakulniyom, Mayuree; Khemthongcharoen, Numfon; Pattamang, Pattaraluck; Atthi, Nithi; Promptmas, Chamras; Uawithya, Panapat; Jeamsaksiri, Wutthinan (My University, 2021)
This paper is aimed to propose a numerically designed multiple dilution microfluidic chip that can simultaneously deliver several serum dilutions in parallel. The passive mixing scheme is selected for dilution and achieved by the serpentine mixing channel in which Dean vortices are induced to increase the contact area and time for better diffusion. The mixing performance at the exit of this dilution chip is numerically evaluated using five commonly-used mixing indices with the goal that the homogeneity of the mixture over the exit cross-sectional area of the mixing channel must be greater than 93.319% to fulfill the six-sigma quality control.
Keywords: Dilution; Human serum; Microfluidics; Mixing flow; Mixing index